Case Study on an Alcoholic Respondent - Tinni Dutta (Selected Topics in Humanities and Social Sciences Vol. 7, 2021)
Case study refers to intensive investigation of case highlighting different dimension. In this present study the case was admitted in a reputed de-addiction/rehabilitations center, Kolkata, India. This case study implies a retrospective archival approach. Case history was taken thoroughly and psychological tests were administered to corroborate findings with case history. Amal was admitted in the centre with the chief complaints of consuming alcohol which hampers his physical, emotional, occupational and social life. The criteria for alcohol intoxication include drinking and significant maladaptive behavioural changes - such as inappropriate aggressive behaviour, mood labiality, impaired judgment in family and occupational spheres shortly after alcohol consumption. He denies of his problems and often becomes defensive. Detection of alcoholism in this particular case was done by CAGE Test. The person is suffering from ‘Psychoactive Substance Abuse Disorder’ associated with secondary depression. Considering case history, behaviour and findings of test it implied he has psychopathology. He has undergone therapeutic intervention. Cognitive behaviour therapy was provided to him to strengthen his mental equilibrium.